Один подход к решению оптимизационных задач с вложенной структурой - Лаптин, Ю.П.; Лиховид, А.П. (Теорія оптимальних рішень, 2007)
Quasiblock problems with connecting variables, in which every block (subproblem) in turn is a quasiblock problem, are considered. For solving these problems the decomposition scheme based on construction of linear approximations and searching e -optimal solutions of subproblems was proposed. A particular feature of the algorithm is a possibility of coordination of approximations for different subproblems.